Human Telomerase Reverse Transcriptase as a Therapeutic Target of Dihydroartemisinin for Esophageal Squamous Cancer - Li, Qingrong; Ma, Qiang; Xu, Lei; Gao, Chuanli; Yao, Lihua; Wen, Jilin; Yang, Miyuan; Cheng, Jibing; Zhou, Xi; Zou, Jiang; Zhong, Xiaowu; Guo, Xiaolan (Frontiers in Pharmacology, 2021)
Objective:To elucidate the oncogenic role of human telomerase reverse transcriptase (hTERT) in esophageal squamous cancer and unravel the therapeutic role and molecular mechanism of dihydroartemisinin (DHA) by targeting hTERT. Methods:The expression of hTERT in esophageal squamous cancer and the patients prognosis were analyzed by bioinformatic analysis from TCGA database, and further validated with esophageal cancer tissues. The Cell Counting Kit-8 (CCK8),colony formation assay,transwell assay,and scratch assay were used to evaluate the proliferation and migration abilities of esophageal squamous cancer cells after hTERT overexpression or treated with indicated concentrations of DHA. Fluorescence microscopy and flow cytometry were conducted to measure the intracellular reactive oxygen species (ROS) levels in cancer cells after treated with DHA. Moreover, RT-PCR and Western blot were performed to test the alteration of associated genes on mRNA and protein level in DHA treated esophageal cancer cells. Furthermore,tumor-bearing nude mice were employed to evaluate the anticancer effect of DHA in vivo. Results:We found that hTERT was significantly upregulated in esophageal squamous cancer. Overexpression of hTERT evidently promoted the proliferation and migration of esophageal cancer cells in vitro. Moreover, DHA could significantly inhibit the proliferation and migration of esophageal cancer cells in vitro, and significantly down-regulate the expression of hTERT in a time- and dose-dependent manner. Further studies showed that DHA could induce intracellular ROS production and down-regulate SP1 expression, a transcription factor that bound to the promoter region of hTERT gene. Moreover, overexpression of SP1 evidently promoted the proliferation and migration of Eca109 and TE1 cells. Intriguingly, rescue experiments showed that inhibiting ROS by NAC alleviated the downregulation of SP1 and hTERT in cells treated with DHA. Furthermore, overexpression of SP1 or hTERT could attenuate the inhibition effect of DHA on the proliferation and migration of esophageal cancer cells. In tumor-bearing nude mice model, DHA significantly inhibited the growth of esophageal squamous cancer xenografts，and downregulated the expression of SP1 and hTERT protein, while no side effects were observed from heart, kidney, liver, and lung tissues by HE stain. Conclusions:hTERT plays an oncogenic role in esophageal squamous cancer and might be a therapeutic target of DHA through regulating ROS/SP1 pathway.